Effect of entomopathogens on Africanized Apis mellifera L. (Hymenoptera: Apidae) - Potrich,Michele (2018)
ABSTRACT This study aimed to evaluate the effect of commercially used entomopathogens on Africanized Apis mellifera L. (Hymenoptera: Apidae). Four bioassays were performed: 1) pulverized entomopathogens on A. mellifera; 2) entomopathogens sprayed on a smooth surface; 3) entomopathogens sprayed on soy leaves; and 4) entomopathogens mixed with candy paste (sugar syrup). Five treatments were prepared: sterile distilled water (control), distilled water sterilized with Tween® 80 (0.01%), and the commercial entomopathogens Metarhizium anisopliae E9 (1.0 × 109 conidia mL−1), Beauveria bassiana PL63 (1.0 × 108 conidia mL−1) and Bacillus thuringiensis var. kurstaki HD-1 (3.0 × 108 spores mL−1). Each treatment consisted of five repetitions, with 20 workers per repetition, which were stored in a plastic box and, later, in a biological oxygen demand (B.O.D.) incubator (27 ± 2 ºC, RH of 60% ± 10%, 12-h photophase). The mortality of the workers was evaluated from 1 h to 240 h, and the data were analyzed using Bayesian inference. The workers killed by the ingestion of candy paste contaminated with the pathogens (products) were randomly separated and selected for the removal of the midgut. Each midgut was fixed in Bouin's solution and prepared for histology. B. bassiana was verified to reduce the survival of A. mellifera workers in all bioassays. Moreover, M. anisopliae reduced the survival of A. mellifera workers directly sprayed, on a smooth surface and mixed with candy. B. thuringiensis reduced A. mellifera survival on a smooth surface and mixed with candy paste. However, its effects were lower than that observed by B. bassiana. The treatments with the biological products did not induce morphometric alterations in the midgut of A. mellifera.